Modification of LSC spectra of 125I by high atomic number elements. (September 2018) - Shoji, M.; Aso, T.; Hara, M.; Benii, R.; Kato, Y.; Furusawa, T.; Yoshimura, T.
Abstract: The 125 I pulse-height spectra via a liquid scintillation counter (LSC) displayed notable variations. The counting efficiencies of higher and lower energy peaks increased and decreased, respectively, with the enhancement of the amount of high atomic numbered elements within the cocktails. This tendency was ascribed to the increasing probability of the interaction of photons with the scintillation cocktail. Moreover, it was noted that the shape of a 125 I spectrum strongly depends on the amount of high atomic numbered elements. Highlights: The influence of cocktail components on 125 I pulse-height spectra was studied. The spectra with Hionic-Fluor differed significantly from other cocktails. Modification by varying high atomic numbered elements in the cocktail was evaluated. Presence of photon interactions vary LSC spectra, depending upon composition.